2019
DOI: 10.1177/2309499019832665
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gait variability and symmetry in trained individuals with transtibial and transfemoral limb loss

Abstract: Gait variability is a determinant of qualified locomotion and is useful for monitoring the effects of therapeutic interventions. The aim of this study was to compare gait variability and symmetry in trained individuals with transtibial (TT) amputation and transfemoral (TF) amputation. Methods: The design of this study was planned as observational. Eleven individuals with TF amputation, 14 individuals with TT amputation, and 14 healthy individuals (HI) were evaluated with a motorized treadmill. The mean step le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The lack of significant differences between AMP and CON groups for kinematic measures of gait stability has also been reported in previous literature. Keklicek et al found that differences in gait variability was more pronounced in individuals with transfemoral amputation, while individuals with transtibial amputation demonstrated gait patterns similar to those in able-bodied subjects [33]. Similarly, our findings across individuals in the AMP group corroborate the findings of Parker et al, which reported no differences in gait variability between individuals with dysvascular or non-dysvascular amputation [34].…”
Section: Discussionsupporting
confidence: 89%
“…The lack of significant differences between AMP and CON groups for kinematic measures of gait stability has also been reported in previous literature. Keklicek et al found that differences in gait variability was more pronounced in individuals with transfemoral amputation, while individuals with transtibial amputation demonstrated gait patterns similar to those in able-bodied subjects [33]. Similarly, our findings across individuals in the AMP group corroborate the findings of Parker et al, which reported no differences in gait variability between individuals with dysvascular or non-dysvascular amputation [34].…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, using three sensors (MIMUs mounted on the trunk and shanks), the method proposed in the present study achieved similar to improved accuracy (mean NRMSE) and better precision (standard deviation of the NRMSE) compared to the method proposed by Shahabpoor and coworkers using the acceleration of three different segments (trunk, pelvis and a thigh) in healthy participants (present study vs. healthy participants: 11.6 ± 2.1% vs. 16 ± 2.0% in the anteroposterior direction, 21.5 ± 2.7% vs. 18 ± 6.7% in the mediolateral direction and 7.7 ± 0.4% vs. 7 ± 1.7% in the vertical direction). Although walking variability for people with lower-limb amputation is higher with respect to typical gait [ 55 ], it may be speculated that the increased precision in the present study could be related to the fact that only intra-subject variability was considered since a single participant was tested. Conversely, six asymptomatic subjects ambulating at different walking speeds were recruited in [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stance times tended to be shorter on the prosthetic limb compared with the intact limb, with more symmetry in individuals who used transtibial prostheses than transfemoral prostheses. Three studies in this review compared stance time symmetries and found the greatest symmetry in individuals without limb loss, followed by individuals who used transtibial prostheses (89.7%–93.4%), and then individuals who used transfemoral prostheses (58.6%–74.5%) 16,34,35,48 . However, individuals without limb loss and individuals who used transtibial prostheses tended to have similar amounts of symmetry in studies included in this review.…”
Section: Discussionmentioning
confidence: 86%
“…Three studies in this review compared stance time symmetries and found the greatest symmetry in individuals without limb loss, followed by individuals who used transtibial prostheses (89.7%-93.4%), and then individuals who used transfemoral prostheses (58.6%-74.5%). 16,34,35,48 However, individuals without limb loss and individuals who used transtibial prostheses tended to have similar amounts of symmetry in studies included in this review. Individuals who used transfemoral prostheses tended to have the widest range of symmetry across studies with the lowest minimum values.…”
Section: Spatiotemporal Parametersmentioning
confidence: 96%